MEMBANGUN MANAJEMEN DAN BIMBINGAN KONSELING RESPONSIF DISEKOLAH MENENGAH PERTAMA STUDI KASUS DI SMP 3 CIPATAT - Nina Ambarawati; Sri Handayani; Eva Dianawati Wasliman (STKIP Subang, 2025)
Student problems at the junior high school level are becoming increasingly complex, encompassing academic, social, emotional, and behavioral aspects, thus requiring guidance and counseling (GC) services that are managed systematically and responsively. However, the management of GC services in schools still faces challenges related to needs-based planning, institutional coordination, and measurable service evaluation. This study aims to analyze responsive guidance and counseling management in addressing student problems at SMP Negeri 3 Cipatat based on the management functions of planning, organizing, actuating, and controlling (POAC). This research employed a qualitative approach using a case study method. Data were collected through in-depth interviews with the principal, guidance and counseling teacher, homeroom teachers, subject teachers, and students, complemented by observation and document analysis. Data analysis was conducted interactively through data reduction, data display, and conclusion drawing, with triangulation applied to ensure data validity. The results indicate that guidance and counseling management at SMP Negeri 3 Cipatat has practically implemented the POAC functions and demonstrates a responsive approach to students’ needs. Service planning is based on needs analysis through student needs assessment questionnaires and observation, although it is constrained by data validity and the limited professional experience of the counseling teacher. The organizing and implementation of services are carried out collaboratively; however, evaluation remains process-oriented and has not yet applied outcome-based indicators. This study concludes that strengthening guidance and counseling management is still required to ensure more effective and sustainable services.